Village Organization Communication Against Tidal Flooding - Rafiqah Yusna Siregar; Afriadi Amin; Regi Novfitri (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to investigate the role of organizational communication in mitigating tidal flood disasters in Nelayan Indah Village, Medan Labuhan District, Indonesia. The village frequently experiences tidal floods due to its low-lying coastal location and aging embankments. Employing a qualitative descriptive method, the research collected data through participatory observation, interviews with key stakeholders (village heads, subdistrict officials, and residents), and documentation. The study applies the POAC framework (Planning, Organizing, Actuating/Directing, Controlling) integrated with a community-based communication (CBC) approach. Findings indicate that community involvement in infrastructure development, localized messaging, and inter-agency collaboration significantly improve the effectiveness of flood mitigation. However, several challenges persist, including the absence of hazard maps, limited digital access, low public awareness, and inadequate feedback mechanisms. The study emphasizes the need for participatory, data-driven communication strategies that are sensitive to socio-cultural contexts. Theoretically, this research extends the POAC framework to community-based disaster communication, an area that has rarely been explored in the literature. Practically, the study offers policy recommendations for participatory organizational communication models. These models aim to enhance the resilience of coastal communities against tidal floods. Thus, the study provides new insights into the strategic role of grassroots organizational communication in disaster mitigation.